Fenton art glass a centennial of glass making 1907 to 2007 and beyond - Coe, Debbie; Coe, Randy (Atglen, PA : Schiffer Pub., 2012)
For the first time, beautiful glass from 100 years of Fenton production are shared in one book. Diversity is highlighted, showing over 3000 items in more than 575 color photos. Detailed captions include descriptions with up-to-date values. Chocolate, Opalescent, Carnival, Stretch, Art Glass, Hobnail, Burmese, Rosalene, Animals, and Holiday related items are featured in old and new styles. It has something for everyone. A brief history of the company is given along with information on the Fenton family, decorators and glass workers. A detailed collector list, bibliography, and index make this a useful reference.
1907 to 1909: The beginning years -- 1910 to 1919: Carnival and stretch years -- 1920 to 1929: The age of color -- 1930 to 1939: The time of struggle -- 1940 to 1949: The War years -- 1950 to 1959: Milk glass and more -- 1960 to 1969: A new age of color -- 1970 to 1979: The revival -- 1980 to 1989: Moving forward and looking back -- 1990 to 1999: Dawn of a new age -- 2000 to 2007: Another century begins -- 2010 to 2012: Struggles and disappointments -- Collector information.
Includes bibliographical references and index.
108226
Keywords: Fenton Art Glass Company; Fenton Art Glass Company; 1900-1999; Glassware -- West Virginia -- Williamstown -- History -- 20th century; Glassware -- United States; Glassware -- Collectors and collecting -- United States